CPAP Titration Pressure in Split-Night, Full-Night, and Home Auto-Titration: A Prospective Comparative Analysis of Patients With Moderate to Severe Obstructive Sleep Apnea - Park SI; Choi W; Lee C; Kim HY; Jung YG (Nature and Science of Sleep)
Song I Park,1 Woori Choi,2 ChangHee Lee,3 Hyo Yeol Kim,3 Yong Gi Jung3 1Department of Otolaryngology-Head and Neck Surgery, Inje University Ilsan Paik Hospital, Inje University College of Medicine, Goyang, Republic of Korea; 2Department of Otorhinolaryngology-Head and Neck Surgery, Samsung Changwon Hospital, Sungkyunkwan University School of Medicine, Changwon-si, Republic of Korea; 3Department of Otorhinolaryngology-Head and Neck Surgery, Samsung Medical Center, Sungkyunkwan University School of Medicine, Seoul, Republic of KoreaCorrespondence: Yong Gi Jung, Department of Otorhinolaryngology-Head and Neck Surgery, Samsung Medical Center, Sungkyunkwan University School of Medicine, 81 Irwon-ro, Gangnam-gu, Seoul, 06351, Republic of Korea, Tel +82 2 3410 3577, Fax +82 2 3410 6987, Email ent.jyg@gmail.comPurpose: This prospective study aimed to compare titration pressures obtained using three methods—full-night titration (FN-T), split-night titration (SN-T), and home auto-titration (HA-T)— in patients with moderate to severe obstructive sleep apnea (OSA). Additionally, factors contributing to pressure differences relative to FN-T were investigated.Methods: SN-T was performed on 74 patients suspected of having OSA. Those diagnosed with moderate to severe OSA who completed SN-T underwent HA-T for 2– 3 weeks. FN-T was then performed on patients who adhered to HA-T for at least 70% of prescribed nights. Ultimately, 29 patients met the inclusion criteria. Titration pressures from SN-T (SN-TP), HA-T (mean pressure [HA-TPm] and 90th percentile pressure [HA-TP90]), and FN-T (FN-TP) were compared using the Wilcoxon signed-rank test. Patients were classified into pressure disparity and non-disparity groups based on differences between FN-TP and the other methods. Logistic regression analyses were performed to identify factors associated with pressure differences. Baseline characteristics in subgroup analyses were compared using independent t-tests or Mann–Whitney tests for continuous variables and Fisher’s exact tests for categorical variables.Results: The titration pressures for SN-TP, FN-TP, HA-TP90, and HA-TPm were 8, 9, 9.6, and 8.1 cm H2O, respectively. All pressures correlated significantly with FN-TP (p < 0.05). HA-TP90 was significantly higher than FN-TP (p < 0.05), while FN-TP was higher than SN-TP (p < 0.05), with similar trends observed at the individual level. Nasal septal deviation (odds ratio 16.63, p = 0.018) and high apnea-hypopnea index (odds ratio 1.06, p = 0.027) were identified as predictors of pressure differences.Conclusion: This study is the first to directly compare multiple titration pressures to standard FN-TP in the same patients. SN-T and HA-T are reliable alternatives to FN-T in moderate to severe OSA, though predictors of significant pressure variance require careful consideration.Keywords: split-night titration, auto-titration, full-night titration, pressure, obstructive sleep apnea, polysomnography